Development of a short form of Mini-Mental State Examination for the screening of dementia in older adults with a memory complaint: a case control study - Haubois, Gladys (BioMed Central, 2011)
BACKGROUND: Primary care physicians need a brief and accurate screening test of dementia. The objective of this study was to determine whether a short form of Mini-Mental State Examination (SMMSE) was as accurate as the Mini-Mental State Examination (MMSE) in screening dementia. METHODS: Based on case control design study, SMMSE and MMSE were assessed in 184 community-dwelling older adults (mean age 81.3 ± 6.5 years, 71.7% women) with memory complaint sent by their primary care physician to a memory clinic. Included participants were separated into two groups: cognitively healthy individuals and demented individuals. RESULTS: The trade-off between sensitivity and specificity of the SMMSE for clinically diagnosed dementia was 4. Based on the cut-off value ≤ 4 for SMMSE and a cut-off value ≤ 24 for MMSE, the sensitivity of both tests was similar (89.5% for SMMSE versus 90.0% for MMSE), whereas the specificity, the positive predictive values (PPV) and the negative predictive values (NPV) were higher for SMMSE compared to MMSE (85.4 versus 75.5% for specificity; 95.5% versus 92.8% for PPV; 70.0 versus 68.9 for NPV). The positive and negative Likehood Ratio (LR) of SMMSE were higher than those of MMSE (respectively, 6.1 versus 3.7; 8.1 versus 7.7). In addition, odds ratio (OR) for dementia was higher for the SMMSE compared to the MMSE (OR = 49.8 with 95% confident interval (CI) [18.0; 137.8] versus OR = 28.6 with 95% CI [11.6; 70.3]). CONCLUSIONS: SMMSE seems to be an efficient short screening test for dementia among community-dwelling older adults with a memory complaint. Further research is needed to confirm its predictive values among unselected primary care older patients.